PENERAPAN KEPUTUSAN VERSTEK DI PENGADILAN AGAMA - Darmawati, Darmawati; Zainuddin, Asriadi (Al-Mizan, 2015)
Implementation of verstek decision in the Religious Court is one of the decision which handed down by the judges in the court. Verstek decision, is the decision which handed down because the absence of the defendant even though the defendant himself has been summoned by the proper and authorized. Verstek decision will be handed down after the parties were called and examined his case and examine whether the matters raised by the plaintiff it can be proved and the authority of the Religious Court. In the verdict verstek, then demand can be granted if the suit was groundless and did not fight right. But if the suit was groundless and or against the rights, the decision of the judge verstek a statement that the plaintiffs claim is not accepted, and if the claim is granted with verstek verdict, the defendant may seek such objection with verzet.